TOTAL QUALITY MANAGEMENT: CAPAIAN KUALITAS OUTPUT MELALUI SISTEM KONTROL MUTU SEKOLAH - Aminatul Zahroh (Cendekia: Jurnal Pendidikan dan Pembelajaran, 2015)
This paper describes Total Quality Management (TQM) that deescribes how quality would be achieved through control porcess in the education practices.  Quality refers to structured process to improve the outputs. To accomplish standardized quality of an output, all school components are required in a networking involving principals, teachers, students, staffs, and students-parents.  Education quality should serve input and porcess to achieve standardized quality of the output.  Essentially, TQM is a core management to see quality control from process into quality.